2021
DOI: 10.1002/rth2.12485
|View full text |Cite
|
Sign up to set email alerts
|

Vascular thromboembolic events following COVID‐19 hospital discharge: Incidence and risk factors

Abstract: Background Coronavirus disease 2019 (COVID‐19) is associated with high rates of thromboembolic events in hospitalized patients. It remains to be determined if this risk persists following hospital discharge. Methods We conducted a retrospective cohort study of outpatients recently hospitalized for COVID‐19 to determine the incidence of vascular thromboembolic events within 30 days of discharge. We investigated the risk factors associated with these events, including intensive care admission, age, and anticoagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 5 publications
2
36
1
Order By: Relevance
“…Of the 120 publications (Table 2 ), 67 (55.9%) presented original data as follows: 43 (35.9%) were original articles/papers [ 20 62 ]. Fifteen (12.5%) publications were short articles with original data, as follows: 7 brief communications/reports [ 63 69 ] (5 cohort and 1 cross-sectional studies, and 1 case series), 1 commentary [ 70 ] (cross-sectional study), 6 letters to editors [ 71 76 ] (4 cross-sectional and 1 cohort studies, and 1 case series), and 1 short communication [ 77 ]. Fifty-four (45%) articles did not present original data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 120 publications (Table 2 ), 67 (55.9%) presented original data as follows: 43 (35.9%) were original articles/papers [ 20 62 ]. Fifteen (12.5%) publications were short articles with original data, as follows: 7 brief communications/reports [ 63 69 ] (5 cohort and 1 cross-sectional studies, and 1 case series), 1 commentary [ 70 ] (cross-sectional study), 6 letters to editors [ 71 76 ] (4 cross-sectional and 1 cohort studies, and 1 case series), and 1 short communication [ 77 ]. Fifty-four (45%) articles did not present original data.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-nine (49.2%) articles presented signs and symptoms of Long COVID. Twenty-three (19.2%) articles reported on the generalized signs/symptoms (21 adults, 2 pediatrics), and the remaining 36 (30%) articles focused on specific organs/systems (9 focused on thromboembolism [ 29 , 30 , 36 , 50 , 66 , 69 , 114 , 117 , 118 ], 8 respiratory [ 23 , 27 , 37 , 41 , 44 , 67 , 75 , 127 ], 4 neurology [ 46 , 61 , 102 , 116 ], 2 musculoskeletal [ 53 , 72 ], 5 cardiovascular [ 39 , 49 , 54 , 112 , 120 ], 3 mental health [ 21 , 58 , 108 ], 2 Multisystem Inflammatory Syndrome [MIS] [ 43 , 113 ] (one about pediatrics MIS [ 43 ] and one on adults MIS [ 113 ]), 1 skin manifestations [ 70 ], 2 were exclusively about post-acute infectious fatigue [ 33 , 122 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The American College of Chest Physicians has previously defined a threshold symptomatic thrombotic risk of 1.0% in control groups to define an “at‐VTE” or “moderate‐VTE” risk hospitalized medically ill population that would benefit from pharmacologic thromboprophylaxis. 2 Although it should be acknowledged that the rate of symptomatic pulmonary emboli in the study by Eswaran et al 1 was ≈0.7%, nearly half of the population had received postdischarge thromboprophylaxis. In addition, applying the criteria used by the authors to define a 2.0% symptomatic thrombotic incidence as “low risk,” no hospitalized medically ill patient—including those with pneumonia and sepsis—would in theory benefit from in‐hospital pharmacologic thromboprophylaxis, as the incidence of symptomatic VTE seen in control groups in the early pivotal trials of thromboprophylaxis in hospitalized medically ill patients was ≈1.5%.…”
mentioning
confidence: 95%
“…We read with interest the retrospective cohort study by Eswaran et al 1 that found a 2.0% incidence of symptomatic thromboembolic events in a cohort of 447 hospitalized patients with coronavirus disease 2019 (COVID‐19) within 30 days of discharge. These events encompassed both arterial and venous thromboembolic events (ATEs and VTEs), including four non–ST‐segment–elevation myocardial infarctions, three pulmonary emboli, one ischemic stroke, and one splenic infarct.…”
mentioning
confidence: 99%